Studi Karakteristik Morfologis Aksesi Rumput Benggala (Panicum Maximum) yang Tumbuh di Wilayah Kota Jambi - Yun Alwi; Ahmad Yani; Ubaidillah Ubaidillah (Universitas Batanghari Jambi, 2022)
This study aims to evaluate the characteristics of accession of Bengal grass that grows in the city of Jambi. The research was conducted in two stages, namely the field observation stage to obtain qualitative data and quantitative data related to the characteristics of Bengal grass. The results of the observation phase were validated to obtain four accessions that had the same morphological characteristics. There were four accessions which were then planted in polybags in a greenhouse, namely Tlp1, Dns2, Jlt1 and Ktb2 as treatments with repeated 10 times. The design used was a completely randomized design. The parameters observed were plant height, leaf length, leaf width, internode length, number of internodes, stem circumference and leaf color. The results showed that the Jlt1 accession was an accession that had different characteristics (P <0.05) compared to other accessions.